Sosialisasi Keuangan Digital: Literasi Menabung dan Investasi Generasi Muda di Batam - Putera, Dimas Akmarul; Jufri, Muhammad; Adi, Roni; Saputra, Puji Tri (Penerbit Goodwood, 2025)
Purpose: This program aimed to strengthen digital financial literacy among youth in Batam, focusing on safe and practical savings and investment strategies that are aligned with current technologies. Methodology/approach: The community service program (PKM) was conducted in three stages: preparation (materials, partner coordination, outreach), implementation (talks, hands-on use of e-wallets/auto-debit/micro-investing apps, discussions), and evaluation (pre- and post-questionnaires and feedback). Results/findings: Most participants rated the materials as clear and useful, and many reported better knowledge and readiness to adopt digital saving and try beginner-friendly instruments introduced during the session. The participants represented diverse ages and education levels and included students and MSMEs. Conclusions: The PKM program effectively enhanced digital financial literacy and motivated participants to manage their finances in a modern context. Most participants clearly understood the material, found it relevant, and showed improved knowledge and readiness to save and invest digitally. Despite challenges related to time constraints and varying levels of digital literacy, the program positively influenced the adoption of wise financial behavior in the technological era. Limitations: Short duration, varied baseline literacy, and intermittent Internet access limited deeper practice; long-term behavioral outcomes were not tracked. Contribution: The PKM effectively improved essential competencies in digital money management and encouraged prudent technology-enabled behaviors among youth. We recommend follow-up coaching and long-term monitoring to consolidate saving habits and safe, small-ticket investing.